THE PHENOMENON OF SILVIO BERLUSCONI - Kovaleva, A. Y. (Vestnik MGIMO-Universiteta, 2016)
Silvio Berlusconi, former Italian Prime Minister, is about to turn 80 this September. He has dominated Italian politics since 1994 and is now Italy's longest-serving PM since Mussolini. He has survived countless forecasts of his imminent departure. Political researchers argue that despite his personal success, he has been a disaster as a national leader. Nevertheless, to call Berlusconi a failure would be absurd, particularly in terms of his political presence. Having provided the country with four governments that lasted for a total of almost ten years, Berlusconi left a profound mark on Italian political history and even defined the era of Berlusconism. This article is based on the assumption that there is considerable political substance to Berlusconism, the substance of Berlusconi's public discourse. In 1994 he launched "Forza, Italia", a political party that within the span of a couple of months would become one of the biggest in Italy. From the outset, the party has evoked both praise and criticism amongst political communications scholars. Most of the discussion was centered on party's antiestablishment rhetoric, its lack of traditional organization, consistent political agenda and controversial nature of the main leader. Interestingly, the celebratory interpretations surrounding the Berlusconi phenomenon have focused on the leaders' ability to create a mass support base primarily through the use of TV; all of this whilst bypassing traditional institutions. This article is about the communicational strategy Berlusconi employed and why it was successful. Berlusconism is a true political phenomenon, which deserves to be analyzed carefully.